Iron uptake by Escherichia coli in urinary tract infections and urosepsis. - Beata Krawczyk; Paweł Wityk; Agnieszka Laskowska; Anna Stanisławska-Sachadyn; Joanna Raczak-Gutknecht; Małgorzata Waszczuk-Jankowska; Magdalena Burzyńska; Marek Bronk; Tomasz Majchrzak; Michał J Markuszewski (PLoS ONE, 2025)
The pathogenesis of urosepsis in uncomplicated and community-acquired urinary tract infections (UTIs) caused by Escherichia coli was studied. We hypothesized that siderophores involved in iron uptake may determine bacterial adaptation to the urine and blood environment in patients with UTI, leading to urosepsis. E. coli isolates were compared from urosepsis patients (cases) and UTI (control group). The patterns of bacterial DNA fingerprints isolated from the blood and urine of patients with urosepsis were compared by PCR melting profile method to detect urosepsis and exclude nosocomial infection. Chromium Azurol S (CAS) assay and RT-qPCR were used to investigate the expression levels of siderophore genes in artificial urine and M9 supplemented with whole blood. E. coli isolates from artificial urine were proteomically analysed. The pro-inflammatory factors IL-2,4,6,8,10, IFN-gamma, TNF-alpha and CRP were quantified in the patients' serum. PCR detected and co-occurrence of enterobactin, aerobactin and yersiniabactin was significantly more frequent in the urosepsis (P = 0.0039) and with the iha gene may represent markers of urosepsis risk. Aerobactin was dominant in urosepsis (P = 0.03), but its expression in artificial urine was twice higher than in blood (P = 0.03). When cultured in artificial urine, the expression of entC was significantly higher (P = 0.029), while the expression of iro-2, iucA and iroB were lower in strains obtained from urosepsis (P = 0.007; P = 0.030; P = 0.012; respectively) as compared to the UTI group. Ferritin-1, iron uptake system component EfeO, ferrous iron transport protein B, nitrate/nitrite response regulator protein NarL, protein HemY, ferrienterobactin receptor FepA, lipopolysaccharide export system protein LptA and 2Fe-2S ferredoxin were found by proteomic analyses in urosepsis only. A positive association of IL-6,8,10, TNF and CRP proteins with urosepsis was observed. In conclusion, risk factors for UTI-related sepsis may be related to the iron uptake system, and genetic and proteomic profiles may help identify them.